Estimating the Costs of Standardization: Evidence from the Movie Industry - El Hadi Caoui (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies the decentralized adoption of a technology standard when network effects are present. If the new standard is incompatible with the current installed base, adoption may be inefficiently delayed. I quantify the magnitude of "excess inertia" in the switch of the movie distribution and exhibition industries from 35mm film to digital. I specify and estimate a dynamic game of digital hardware adoption by theaters and digital movies supply by distributors. Counterfactual simulations establish that excess inertia reduces surplus by 19% relative to the first-best adoption path; network externalities explain 29% of the surplus loss.
Keywords: L82; L86; O33; 330; technology adoption; network effects; movie industry